Nilai Moral Naskah Drama Liang Karya Puthut Buchori sebagai Alternatif Bahan Ajar Drama di SMA - Malmayang, Febriasni (Universitas PGRI Semarang, 2024)
This research aims to describe moral values play script Liang by Puthut Buchori and moral values play script Liang by Puthut Bucori as an alternative drama teaching materials in Senior High School. This research is a descriptive qualitative. The data was collected using a reading and note taking techniques. The text were analyzed using qualitative descriptive. The result of the study show that the moral value contained in the play Liang by Puthut Buchori is the moral value of human relations with oneself, which is to remain strong even though the storm hits. The moral values of human relations with other humans, namely advising each other, loving each other, helping each other, reminding each other, being aware of mistakes that have been made, fighting for each other, and being fair. The moral value of human relations with God, namely being grateful for the blessings given by God. The moral values contained in the play Liang by PuthutBuchori are appropriate to be used as an alternative for learning drama in high school which are contained in Basic Competence 3.19 Analyzing the content and language of the drama that is read or watched.